Modulation of Immune System by Kaposi’s Sarcoma-Associated Herpesvirus: Lessons from Viral Evasion Strategies - Lee, Hye-Ra; Brulois, Kevin; Wong, LaiYee; Jung, Jae U. (Frontiers in Microbiology, 2012)
Kaposi’s sarcoma-associated herpesvirus (KSHV), a member of the herpesvirus family, has evolved to establish a long-term, latent infection of cells such that while they carry the viral genome gene expression is highly restricted. Latency is a state of cryptic viral infection associated with genomic persistence in their host and this hallmark of KSHV infection leads to several clinical-epidemiological diseases such as Kaposi’s sarcoma (KS), a plasmablastic variant of multicentric Castelman’s disease (MCD), and primary effusion lymphoma (PEL) upon immune suppression of infected hosts. In order to sustain an efficient life-long persistency as well as their life cycle, KSHV dedicates a large portion of its genome to encode immunomodulatory proteins that antagonize its host’s immune system. In this review, we will describe our current knowledge of the immune evasion strategies employed by KSHV at distinct stages of its viral life cycle to control the host’s immune system.